Development and Evaluation of a Qur’an-Integrated Interactive Mathematics E-Module to Enhance Learning Interest in Integers - Sri Kartika; Isnaeni Maryam (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
This study aims to develop and evaluate a Qur’an-integrated interactive mathematics e-module designed to enhance students’ interest in learning integers at the Grade VII level. Employing a Research and Development (R&D) methodology, the module was created using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with students from Class VII B at MTs Ma’arif NU Pituruh. Data collection instruments included expert validation questionnaires, teacher and student response questionnaires, and pre- and post-use learning interest surveys. The expert validation process involved evaluations by subject matter experts, media experts, and religious integration experts, resulting in an overall validity score of 90.56%, categorized as highly valid. Supporting instruments achieved an average validation score of 87.50%, also considered highly valid. Practicality tests involving teachers and students yielded an average score of 81.35%, indicating that the e-module is highly practical for use in classroom settings. The effectiveness test, based on student learning interest before and after implementation, showed a significant increase—from an average of 40.62% to 73.67%—shifting from weak to strong interest. These findings demonstrate that the integration of Qur’anic values with interactive digital learning materials not only supports conceptual understanding but also enhances motivation and spiritual development. Therefore, the developed e-module is deemed valid, practical, and effective for mathematics instruction in Islamic educational contexts and aligns well with the objectives of the Merdeka Curriculum.